Unveiling Partnership Culture in Sharia Banking Regulations - Latifah, Umi (Institut Agama Islam Negeri Parepare, 2024)
Purpose – This study investigates whether the regulatory framework governing Sharia banks effectively enforces their distinctive characteristics and fulfills the objectives of maqashid sharia, amid concerns about their perceived similarity to conventional banks. Method – Using a normative legal approach, the research employs qualitative descriptive methods to analyze primary legal frameworks and validate findings through secondary sources. Findings –. The study finds that Indonesia pioneered the concept of Islamic banking in the 1970s, requiring financial intermediation based on a profit-sharing system in accordance with Sharia principles. Despite these mandates, some Sharia banks continue to adopt practices resembling conventional banking markup schemes. Practical implications – The findings highlight the need for legal reforms to reinforce Sharia banks' adherence to their foundational principles, thereby promoting a genuine partnership culture based on the principle of taawun (mutual cooperation). Originality/value – This research underscores the gap between regulatory mandates and practical implementation, offering insights into how legal adjustments can align Sharia banking practices more closely with their philosophical roots